2022
DOI: 10.1016/j.sapharm.2021.08.007
|View full text |Cite
|
Sign up to set email alerts
|

Educating pharmacy students through a pandemic: Reflecting on our COVID-19 experience

Abstract: The impact of the COVID-19 pandemic on pharmacy education worldwide has been immense, affecting students, educators and regulatory agencies. Pharmacy programmes have had to rapidly adapt in their delivery of education, maintaining standards while also ensuring the safety of all stakeholders. In this commentary, we describe the challenges, compromises and solutions adopted by our institution throughout the pandemic, the lessons learnt, adaptive measures taken, and strategies to develop and future-proof our curr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…In the current study, pharmacy students found that course examinations were more challenging during e-learning, which could be attributed to the efforts of instructors to maintain academic integrity, as well as students' deteriorating mental health and dissatisfaction with e-learning [ OL Holden, et al 2021 ]. The findings of the current study revealed that students had divergent viewpoints on the effect of e-learning on peer interaction, which was an unanticipated outcome, given that several studies have indicated that e-learning adversely impacts students' engagement and interaction with peers [ Kaur et al, 2020 , Strawbridge et al, 2022 ]. While e-learning provides the convenience of attending lectures from any location [ Singh V and A Thurman 2019 ], this benefit is not without limitations.…”
Section: Discussionmentioning
confidence: 87%
“…In the current study, pharmacy students found that course examinations were more challenging during e-learning, which could be attributed to the efforts of instructors to maintain academic integrity, as well as students' deteriorating mental health and dissatisfaction with e-learning [ OL Holden, et al 2021 ]. The findings of the current study revealed that students had divergent viewpoints on the effect of e-learning on peer interaction, which was an unanticipated outcome, given that several studies have indicated that e-learning adversely impacts students' engagement and interaction with peers [ Kaur et al, 2020 , Strawbridge et al, 2022 ]. While e-learning provides the convenience of attending lectures from any location [ Singh V and A Thurman 2019 ], this benefit is not without limitations.…”
Section: Discussionmentioning
confidence: 87%
“…Karattuthodi et al and colleagues, in their Indian study, reported that poor academic performance was observed owing to the immediate shift to the online learning programme ( Karattuthodi et al, 2022 ). However, a blended learning approach composed of online lectures and on-site practical sections was followed in many countries and appreciated through student feedback ( Strawbridge et al, 2022 ). On the other hand, those candidates with poor access to advanced facilities and assistance should be identified and supported ( Saleem et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Because of this, community service has become a major aspect of pharmacy education, leading to increased empathy, cultural competence, and communication skills. The COVID-19 pandemic necessitated the implementation of strict social distancing guidelines [ 6 ]. Colleges of pharmacy transitioned onto virtual platforms through the early stages of the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…In March of 2020, the World Health Organization declared the SARS-CoV-2 viral outbreak, also referred to as the coronavirus disease 2019 (COVID-19), a pandemic. As a result of the COVID-19 pandemic and implementation of strict social distancing guidelines, colleges of pharmacies across the world transitioned classroom environments [ 6 ] and co-curricular activities onto virtual platforms [ 7 , 8 , 9 ], which resulted in significant challenges for pharmacy students [ 10 ]. The lives of students were dramatically shifted by the pandemic [ 11 ].…”
Section: Introductionmentioning
confidence: 99%